Beyond Clinical Trials in Patients With Multiple Myeloma: A Critical Review of Real-World Results - Bertamini, Luca; Bertuglia, Giuseppe; Oliva, Stefania (Frontiers in Oncology, 2022)
The current strategies for the treatment of multiple myeloma (MM) have improved, thanks to effective drug classes and combination therapies, for both the upfront and relapsed settings. Clinical trials for newly diagnosed transplant-ineligible patients led to the approval of immunomodulatory drugs and proteasome inhibitors in combination with anti-CD38 monoclonal antibodies, to be administered during the induction phase before transplantation and during maintenance treatment, with lenalidomide recommended until relapse. In relapsed/refractory patients, the complex treatment scenario currently includes several options, such as triplets with anti-CD38 mAbs plus IMiDs or PIs, and novel targeted molecules. Comparisons among clinical trials and real-world data showed a good degree of reproducibility of some important results, particularly in terms of overall response rate, progression-free survival, and overall survival. This may help clinicians towards a proper selection of the best treatment options, particularly in real-world settings. However, as compared with the management of real-world settings, clinical trials have some pitfalls in terms of outcome and especially in terms of safety and quality of life. In fact, trials include younger and presumably healthier patients, excluding those with worst clinical conditions due to myeloma features (e.g., renal insufficiency or bone disease, which can impair the performance status) and comorbidities (e.g., cardiac and pulmonary disease), thus resulting in a possible lack of representativeness of data about the patients enrolled. In this review, we analyze comparable and discrepant results from clinical trials vs. real-world settings published in the last 10 years, focusing on different drugs and combinations for the treatment of MM and providing an overview of treatment choices.